ARSITEKTUR SISTEM INFORMASI GOVERNMENT TO GOVERNMENT (G2G) PERENCANAAN DAN PENGANGGARAN BARANG MILIK DAERAH DENGAN METODE UNIFIED SOFTWARE DEVELOPMENT PROCESS - Yuda Syahidin (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
E-Government is often used as a framework in carrying out government operations, by utilizing the help of information and communication technology, which has been growing rapidly. The Regional Property Management is a form of Government to Government that manages management from headquarters to regional offices. The process of designing the architectural system is intended to assist the Regional Property Management Systems adjusted with 13 Cycles Regional Property Management based on Permendagri No. 17 of 2007. The method used in designing the Information System Architecture is the method of Unified Software Development Process. This method is used to building a framework that is used to developing an application. The process of Software development is divided into several phases, in which in each phases is carried out several stages repeatedly. The research process is done by designing the architecture information system of the region's property management system about planning and budgeting, which still refers to government regulation. Keywords— government to government, system architecture, Unified Software Development Process, framework.